Phosphorylation of group I metabotropic glutamate receptors in drug addiction and translational research - Mao, Li-Min (J Transl Neurosci (Beijing), 2016)
Protein phosphorylation is an important posttranslational modification of group I metabotropic glutamate receptors (mGluR1 and mGluR5 subtypes) which are widely distributed throughout the mammalian brain. Several common protein kinases are involved in this type of modification, including protein kinase A, protein kinase C, and extracellular signal-regulated kinase. Through constitutive and activity-dependent phosphorylation of mGluR1/5 at specific residues, protein kinases regulate trafficking, subcellular/subsynaptic distribution, and function of modified receptors. Increasing evidence demonstrates that mGluR1/5 phosphorylation in the mesolimbic reward circuitry is sensitive to chronic psychostimulant exposure and undergoes adaptive changes in its abundance and activity. These changes contribute to long-term excitatory synaptic plasticity related to the addictive property of drugs of abuse. The rapid progress in uncovering the neurochemical basis of addiction has fostered bench-to-bed translational research by targeting mGluR1/5 for developing effective pharmacotherapies for treating addiction in humans. This review summarizes recent data from the studies analyzing mGluR1/5 phosphorylation. Phosphorylation-dependent mechanisms in stimulant-induced mGluR1/5 and behavioral plasticity are also discussed in association with increasing interest in mGluR1/5 in translational medicine.